Regulative Strategies in Arbitration Law Uncitral Model Law on International Commercial Arbitration (UNCITRAL) compared with Arbitration Law of the People’s Republic of China - Trosborg, Anna (HERMES - Journal of Language and Communication in Business, 2004)
This paper is concerned with the laying down of the law in international and domestic arbitration. Interest centres on regulative and constitutive functions, and an analysis of realisation patterns of regulative (directive) acts is reported. The focus is on the linguistic realisation patterns of obligation, prohibition, and permission in terms of modal verbs and constitutive rules. The ﬁndings show that the language of the law characteristically select patterns of directives which are speciﬁc to the legal domain. Face redress typically used in everyday communication as well as business interaction is not a device used in arbitration law. Moreover, the linguistic devices employed differ as regards different parts of the law. Modal verbs are typically applied for action rules, whereas constitutive rules are mainly reserved for stipulation rules and deﬁnition rules. The analysis offers a comparison of Unicitral Model Law and domestic law. Finally, attention is paid to the adequacy of the chosen linguistic realisation patterns as regards simpliﬁcation/ easiﬁ cation of legal expressions. The results are compared to those obtained in a previous study of Contract Law.